The Use of Video Blogging (Vlogging) In Teaching XII Grade Students’ Speaking Skill at Senior High School - Indriyanti, R. Anissa; Ulfa, Siti Maria (Institut Agama Islam Negeri Palopo, 2025)
This study investigated the application of video blogging (vlogging) in teaching speaking skills to students of Senior High School. The purpose of this study was to explore whether vlogging can be used as a learning aid to progress students' pronunciation, fluency, clarity, and confidence in speaking English. A qualitative approach with a case study design was used on students of Senior High School. Data collection methods included classroom observation, student interviews, and analysis of students' vlog performance over some time. The results showed that vlogging significantly contributed to educating students' speaking skills. Through continuous practice with video recordings, students bigger their speaking confidence, better their pronunciation, and bigger their fluency. In addition, vlogging facilitated the learning process by allowing students to assess themselves and receive feedback from their peers. This study concluded that incorporating video blogging into English classes can be a positive strategy to progress students' speaking skills. The study suggests that teachers should incorporate video blogging into their lessons to create a more engaging and interactive learning environment.